Short Communication: Investigation of Diphtheria in Indonesia: dtxR and tox genes analysis of Corynebacterium diphtheriae collected from outbreaks (Biodiversitas Journal of Biological Diversity, 2017)
Mulyastuti Y, Rahayu SI, Sunarno S, Santoso S, Wasito EB. 2017. Short Communication: Investigation of Diphtheria in Indonesia: dtxR and tox genes analysis of Corynebacterium diphtheriae collected from outbreaks. Biodiversitas 18: 784-787. Diphtheria outbreaks have sporadically occurred in Indonesia recently. It is suspected that toxin profile changes play an important role in vaccine efficacy and the occurrence of outbreaks. This study aimed to investigate the genetic changes of dtxR and tox genes in Corynebacterium diphtheria in Indonesia. Four C. diphtheriae toxigenic isolates circulating in current outbreak area were analyzed by comparing DNA sequences of their dtxR and tox genes to those of the PW8 vaccine strain. Among the four isolates, three point mutations were detected in dtxR gene while three other point mutations were detected in the tox gene. All six were silent mutations, suggesting that the diphtheria toxin is highly conserved at the amino acid sequence level, and indirectly indicating that the vaccine remains appropriate. Genetic variation in dtxR and tox genes of C. diphtheriae isolates from the recent outbreaks in Indonesia was detected.
Keywords: Corynebacterium diphtheriae; DNA Sequence Analysis; dtxR gene; tox gene; Indonesia